Differences in nutritional intake from diet and nutritional supplements between urban and rural pregnant women in China: a nationwide cross-sectional study - Fu, Minghan; Zhou, Yun; Yin, Jia; Xie, Zhencheng; Zhang, Qin; Luo, Hongliang; Li, Yitong; Huang, Jiahui; Wang, Zhixu; Ding, Ye (Frontiers in Nutrition, 2026)
IntroductionMaternal nutritional status during pregnancy affects pregnancy outcomes and the lifelong health of mothers and offspring. In China, prenatal dietary habits and nutritional supplement usage vary across geographic regions, socioeconomic strata, and dietary cultures. This study aimed to evaluate and compare dietary and nutrient intakes of urban and rural pregnant women in China, providing baseline data for relevant health guidance and strategies.MethodsThis multi-stage cross-sectional survey recruited 653 healthy urban and rural pregnant women in their second or third trimesters from 2 municipalities and 11 provinces in China. Dietary and nutritional supplement consumption was assessed using a 4-day online diary paired with a food atlas. The total daily intake of each food category, energy, and key nutrients was evaluated based on the Chinese balanced dietary pagoda and the Chinese Dietary Reference Intakes. The Mann–Whitney U test and Chi-square test were utilized to compare urban–rural differences.ResultsIn this study, both urban and rural pregnant women in different trimesters exhibited an inadequate consumption of multiple food categories: potatoes, vegetables, fruits, fish, shrimp, and shellfish, eggs, milk and its products, soybeans and its products, and nuts, while the intake of livestock meat and poultry, and cooking oil were excessive. Energy and protein intake were inadequate, with imbalanced energy contributions of carbohydrates and fats. Micronutrient deficiencies were widespread, with 13.5 ~ 99.2% of individuals falling below their estimated average references, particularly for VA, VB1, VB6, VB9, calcium, magnesium, and iodine. These nutritional challenges were more severe in rural areas than in urban areas.DiscussionIn conclusion, dietary intake of both urban and rural pregnant women in China is highly imbalanced. Even with nutritional supplements in the survey, many pregnant women lack essential nutrients. A scientific nutrition plan should be developed for them, and a diverse and balanced diet is crucial, especially in rural areas.